1991
DOI: 10.7589/0090-3558-27.2.238
|View full text |Cite
|
Sign up to set email alerts
|

Precipitating Antibodies to Epizootic Hemorrhagic Disease and Bluetongue Viruses in White-Tailed Deer in the Southeastern United States

Abstract: From 1981 to 1989, sera were collected from 3,077 white-tailed deer (Odocoileus virginianus) in Georgia and from 1,749 deer from 12 additional states in the southeastern United States. In Georgia, prevalence of precipitating antibodies to epizootic hemorrhagic disease virus (EHDV) and bluetongue virus (BTV), as determined by agar gel immunodiffusion tests, was dependent on physiographic region, age, and year. Overall prevalence of antibodies to EHDV and/or BTV was 11, 33, 48, and 14% for the Mountain, Piedmont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 8 publications
2
28
0
1
Order By: Relevance
“…Zeier et al 29 reported findings of hantavirus IgG antibodies in dogs, cats, hares and deer. The same authors also reported neutralizing antibodies in dogs, cats, pigs and cattle [29][30][31][32][33][34][35] . Ferreira 36 mentioned that domestic animals like cows, lambs, chickens, dogs, cats and pet rodents could become infected by hantavirus, but without a serious risk of contaminate for their owners.…”
Section: Discussionmentioning
confidence: 95%
“…Zeier et al 29 reported findings of hantavirus IgG antibodies in dogs, cats, hares and deer. The same authors also reported neutralizing antibodies in dogs, cats, pigs and cattle [29][30][31][32][33][34][35] . Ferreira 36 mentioned that domestic animals like cows, lambs, chickens, dogs, cats and pet rodents could become infected by hantavirus, but without a serious risk of contaminate for their owners.…”
Section: Discussionmentioning
confidence: 95%
“…Hemorrhagic disease (HD), caused by related viruses in the epizootic hemorrhagic disease and bluetongue virus serogroups (Orbivirus, Reoviridae), has been documented in free-ranging ruminants in North America since 1955 Stallknecht and Davidson, 1992), but only recently has the disease been recognized in Arizona, USA (Noon et al, 2002a, b). In 2001, two mule deer (Odocoileus hemionus) found near Prescott in central Arizona died of hemorrhagic disease; however, the geographic range of HD viruses in Arizona is unknown.…”
mentioning
confidence: 99%
“…Serologic data are typically acquired from serum obtained from whole, fresh blood (Trainer and Jochim, 1969;Stallknecht et al, 1995). However, the efficacy of dried whole blood samples collected on paper strips for HD surveillance in freeranging white-tailed deer has been demonstrated elsewhere (Stallknecht and Davidson, 1992). Paper strip samples are easier to collect, handle, and store than whole blood, which must be centrifuged and refrigerated until analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Four percent of the animals tested on LSSI had antibodies to BTV and none had antibodies to EHDV. Barrier island white-tailed deer populations showed a low annual incidence of BTV and EHDV, possibly making them susceptible to outbreaks should they occur (Stallknecht et al, 1991). Insular conditions of this population may have provided a degree of isolation from BTV and EHDV due to limited-vector flight distance and immigration-emigration barriers.…”
Section: Discussionmentioning
confidence: 99%